ANALYSIS STUDY OF TEA LEAF (CAMELLIA SINENSIS) EXTRACT ABSORBANCE USING UV-VIS SPECTROPHOTOMETER: STUDI ANALISIS ABSORBANSI EKSTRAK DAUN TEH (CAMELLIA SINENSIS) MENGGUNAKAN UV- VIS SPECTROPHOTOMETER - Aulia Putri; Iwan Sugihartono; Anggara Budi Susila; Rahmat Setiawan Mohar (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
Extraction of 20 grams of green tea leaf powder (Camellia Sinensis) using deionized water as solvent was conducted. Then, the green tea leaf powder solution was added with 100 ml of deionized water solvent and boiled at 70oC for 2 hours. The solution that has been boiled is filtered using filter paper. after filtering the solution is centrifuged with a speed of 4000 rpm for 30 minutes to obtain tea leaf extract. Furthermore, the tea leaf extract was tested for absorbance using a UV-Vis Spectrophotometer. Based on the results of the absorbance test, the absorption value of tea leaf extract was obtained in the wavelength range of 200 to 800 nm with maximum absorption at a concentration of 500 ppm at a wavelength of 225 nm with a band gap of 4.09 eV, while at a concentration of 1000 ppm at a wavelength of 214 nm with a band gap of 3.82 eV.